Measuring distance education at a Moroccan university - Fatima-Zohra Iflahen; Mohamed Jaafari; Fatima Ez-Zahra Benkhallouq (Social Sciences and Humanities Open)
The COVID-19 pandemic has significantly disrupted higher education, forcing universities to rapidly adopt technological and digital solutions to maintain their pedagogical roles creating challenges in sustaining adequate contact between academics and students. This study evaluates the capacity of Cadi Ayyad University (UCA) to deliver quality distance education (DE) during the spring 2020 lockdown, focusing on the impact of educational shifts on students, teachers, and administrative staff to develop scalable and shareable practices for future crises. A tripartite methodology included a comparative analysis of UCA's DE systems before and during the lockdown, quantitative surveys of students, faculty, and administrative staff, and synchronous remote interviews with key stakeholders. SPSS-based statistical analysis revealed significant challenges, such as insufficient stakeholder socialization, increased stress, insecurity, and higher dropout rates. The reliance on PDF resources as a cost-saving strategy highlighted the need for continuous faculty training in active learning and improved access to digital platforms. The findings emphasize the urgent need to address these challenges to enhance DE effectiveness at UCA and ensure the future quality of education during crises.